Automatic Exchange of Information (AEoI) for Indonesian Tax Purposes: Economic Analysis of Law Approach (Universitas Negeri Semarang, 2022)
The aim of this paper was to examine the application of the Automatic Exchange of Information (AEoI) agreement through the point of view of Economic Analysis of Law Theory. This study used a normative legal method with a statute approach, conceptual approach, and comparative approach. The result of this study indicated that: first, AEoI has caused a relocation of deposits but has not led to significant repatriation of funds. The least compliant country of AEoI receives incentives in the form of transferring funds from countries that are aggressively implementing AEoI. Hence, in general, it does not change the amount of funds managed abroad. Second, by using game theory: prisoner's dilemma, it is known that the best decision for Indonesia to respond to the AEoI is to conduct a moratorium on the AEoI agreement.